Molecular medicine and viral infections: modern view on the problemand strategy of interrelations - N. V. Ryazantseva (Бюллетень сибирской медицины, 2008)
The lecture presents basic directions of molecular medicine development. Special attention is devoted to prior direction of identification of molecular and genetic markers of predisposition to chronic course of socially important viral infections, development of molecular basis for personalized therapy and outcome prognosis of interrelations between an infect and a human. Analysis of literature data concerning the discussed prob lem and also the results of proper investigations are presented.